Carp Edema Virus Disease (CEVD) / Koi Sleepy Disease (KSD) - Shohreh Hesami; Pedro Viadanna; Natalie K. Steckler; Staci Spears; Patrick M. Thompson; Karen L. Kelley; Roy P. E. Yanong; Ruth Francis-Floyd; Johnny Shelley; Joseph M. Groff; Andy Goodwin; Olga L. M. Haenen; et al. (EDIS, 2015)
Carp edema virus disease is killing wild and cultured varieties of carp and worrying koi enthusiasts and carp aquaculturists in the United States and around the world. The disease causes skin lesions and swelling and is sometimes called “koi sleepy disease” because infected fish become lethargic and unresponsive. This 6-page fact sheet describes symptoms, diagnosis, prevention, and what fish producers, wholesalers, or retailers can do if they suspect carp may have contracted the disease. Written by Shohreh Hesami, Pedro Viadanna, Natalie Steckler, Staci Spears, Patrick Thompson, Karen Kelley, Roy Yanong, Ruth Francis-Floyd, Johnny Shelley, Joseph Groff, Andy Goodwin, Olga Haenen, and Thomas Waltzek, and published by the School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences, October 2015.